Impact of center volume and the adoption of laparoscopic donor nephrectomy on outcomes in pediatric kidney transplantation. (2nd February 2018) - Burg, Jennifer M.; Scott, David L.; Roayaie, Kayvan; Maynard, Erin; Barry, John M.; Enestvedt, C. Kristian
Abstract: Reports for pediatric kidney transplant recipients suggested better outcomes for ODN compared to LDN. Contemporary outcomes stratified by donor type and center volume have not been evaluated in a national dataset. UNOS data (2000‐2014) were analyzed for pediatric living donor kidney transplant recipients. The primary outcome was GF; secondary outcomes were DGF, rejection, and patient survival. Live donor nephrectomies for pediatric recipients decreased 30% and transitioned from ODN to LDN. GF rates did not differ for ODN vs LDN ( P = .24). GF was lowest at high volume centers ( P < .01). Donor operative approach did not contribute to GF. LDN was associated with less rejection than ODN (OR 0.66, CI 0.5‐0.87, P < .01). Analysis of the 0‐ to 5‐yr recipient group showed no effect of ODN vs LDN on GF or rejection. For the contemporary era, there was no association between DGF and LDN in the 0‐ to 5‐yr group (OR 1.12, CI 0.67‐1.89, P = .67). Outcomes of kidney transplants in pediatric recipients following LDN have improved since its introduction and LDN should be the approach for live donor nephrectomy regardless of recipient age. The association between case volume and improved outcomes highlights future challenges in organ transplantation.